Laboratory Markers in the Management of Pediatric Polytrauma: Current Role and Areas of Future Research - Weber, Birte; Lackner, Ina; Braun, Christian Karl; Kalbitz, Miriam; Huber-Lang, Markus; Pressmar, Jochen (Frontiers in Pediatrics, 2021)
Severe trauma is the most common cause of mortality in children and is associated with a high socioeconomic burden. The most frequently injured organs in children are the head and thorax, followed by the extremities and by abdominal injuries. The efficient and early assessment and management of these injuries is essential to improve patients’ outcome. Physical examination as well as imaging techniques like ultrasound, X-ray and computer tomography are crucial for a valid early diagnosis. Furthermore, laboratory analyses constitute additional helpful tools for the detection and monitoring of pediatric injuries. Specific inflammatory markers correlate with post-traumatic complications, including the development of multiple organ failure. Other laboratory parameters, including lactate concentration, coagulation parameters and markers of organ injury, represent further clinical tools to identify trauma-induced disorders. In this review, we outline and evaluate specific biomarkers for inflammation, acid-base balance, blood coagulation and organ damage following pediatric polytrauma. The early use of relevant laboratory markers may assist decision making on imaging tools, thus contributing to minimize radiation-induced long-term consequences, while improving the outcome of children with multiple trauma.